FOC-Based Soft Start of Induction Motors Using Trigonometric S-Curve - Can, Do Van; Van Hieu, Hoang (IAES Indonesian Section, 2025)
This paper presents a novel approach to improving the starting performance of three-phase induction motors by integrating an optimized S-curve acceleration profile based on trigonometric functions into a Field-Oriented Control (FOC) framework. Unlike conventional third- and fifth-order polynomial trajectories that suffer from limited jerk continuity and insufficient mechanical damping, the proposed method ensures smooth transitions in acceleration and jerk using sinusoidal functions. The core contribution of this work lies in the development and application of a second-order continuous trigonometric velocity trajectory that significantly reduces mechanical shocks and current oscillations during motor startup and stop phases. Furthermore, the method is designed for real-time implementation on FPGA hardware, enabling high-resolution pulse-width modulation (PWM) suitable for embedded motion control systems. Simulation and experimental results demonstrate superior motion smoothness, improved torque tracking, and enhanced mechanical reliability compared to traditional methods. This research provides a practical and effective solution for applications requiring precise soft-start/stop capabilities, particularly in elevator systems and other high-performance industrial drives.